2020
DOI: 10.1111/cch.12840
|View full text |Cite
|
Sign up to set email alerts
|

‘What if it were like this?’ Perception of mothers of children with cerebral palsy about the ankle‐foot orthosis of their children: A qualitative study

Abstract: Background: The family-centred approach is fundamental in the therapeutic process of children with cerebral palsy (CP), and the increased competence of parents about therapeutic devices, especially orthoses, can facilitate its implementation, thus intensifying the benefits that this device provides. The aim of this study was to understand the perception of mothers of children with CP in relation to their children's anklefoot orthosis.Methods: This is a qualitative study using thematic content analysis techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Similar to previous research with mothers of children with CP, our participants felt that although AFOs are useful for mobility and positioning, AFOs could benefit from improved aesthetics and comfort. 16 A key difference between the study by Lana et al and our study is the strong focus in our study on the AFO provision process, possibly suggesting that the ease or difficulty of obtaining AFOs may be a location-specific challenge. Our study focused on AFO users and their caregivers in the United States, whereas Lana et al sampled mothers of AFO users in Brazil.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Similar to previous research with mothers of children with CP, our participants felt that although AFOs are useful for mobility and positioning, AFOs could benefit from improved aesthetics and comfort. 16 A key difference between the study by Lana et al and our study is the strong focus in our study on the AFO provision process, possibly suggesting that the ease or difficulty of obtaining AFOs may be a location-specific challenge. Our study focused on AFO users and their caregivers in the United States, whereas Lana et al sampled mothers of AFO users in Brazil.…”
Section: Discussionmentioning
confidence: 68%
“…15 Caregivers have voiced some similar perspectives. Lana et al reported that mothers of children with CP expressed that AFOs improved their child's mobility but wanted more personalization and increased comfort 16 Ankle foot orthoses are commonly used for other disabilities, such as Charcot-Marie-Tooth disease. Individuals with Charcot-Marie-Tooth voiced concerns about functional mobility, pain/ discomfort, choice of AFOs and associated footwear, custom design, and use in practical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Zaino et al (35), who studied the experiences of AFO users with cerebral palsy and their caregivers in the United States and reported a knowledge gap among users about AFO provision, such as the rationale for prescribing a specific type of AFO. Their findings also emphasized the importance of educating families about AFOs to address their challenges and concerns, a perspective also supported by other research (38). Clinical teams can assist parents with navigating practical challenges, such as providing advice regarding clothing/footwear brands that have worked for other families or financial resources to support extraordinary expenses.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, caregivers of children with CP noted that AFOs improved mobility for their children, yet also desired improved comfort and individualization (e.g. colors of device/straps) 29 …”
Section: Discussionmentioning
confidence: 99%